Effect of litter substrates on the performance, carcass traits, and environmental comfort of red-winged tinamou (Rhynchotus rufescens) - Nunes, J. C. (2016)
The study aimed at evaluating the effect of litter substrates on the performance, carcass traits, and environmental comfort of red-winged tinamou (Rhynchotus rufescens). In this experiment, 160 birds, with 100 and 300 days of age, were housed into 20 pens, and distributed according to a completely randomized experimental design into five treatments with four replicates of eight birds each. Treatments consisted of five litter substrates: wood shavings, rice husks, peanut hulls, grass hay, or sand. Feed intake; weight gain; breast, hock, and footpad lesions; back feathering; total meat production; carcass and parts yield; and leukocyte counts were evaluated. Litter substrates were analyzed for dry matter content, standard microbial count, ammonia volatilization potential, water content, water holding capacity, temperature, and radiant heat load. The results showed that litter substrate did not influence the evaluated bird parameters, despite the higher microbial counts and released ammonia values determined in peanut hulls and sand, respectively. Sand also tended to have higher average temperature than the other litter substrates. It was concluded that litter substrate should be chosen at farmer discretion, taking into consideration its cost and utilization after use.